2018
DOI: 10.1002/ccd.27986
|View full text |Cite
|
Sign up to set email alerts
|

An overview of percutaneous coronary intervention in dialysis patients: Insights from a Japanese nationwide registry

Abstract: Objectives This study sought to provide an overview of percutaneous coronary intervention (PCI) in dialysis patients from a Japanese nationwide registry. Background Little is known about dialysis patients undergoing PCI because few are enrolled in clinical trials. Methods We analyzed 624,900 PCI cases including 41,384 dialysis patients (6.6%) from 1,017 Japanese hospitals between 2014 and 2016. We investigated differences in characteristics and in‐hospital outcomes between dialysis and nondialysis patients, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Prior studies showed that lower preprocedural hemoglobin and impaired renal function are associated with worse clinical outcomes after PCI [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. These two factors are crucial for precise risk assessment for adverse outcomes after PCI, namely, mortality and bleeding [15,16], but the combined effects of anemia and impaired renal function have not been thoroughly investigated, especially in contemporary and large PCI registries.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Prior studies showed that lower preprocedural hemoglobin and impaired renal function are associated with worse clinical outcomes after PCI [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. These two factors are crucial for precise risk assessment for adverse outcomes after PCI, namely, mortality and bleeding [15,16], but the combined effects of anemia and impaired renal function have not been thoroughly investigated, especially in contemporary and large PCI registries.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for worse clinical outcomes after PCI in patients with lower hemoglobin and higher creatinine levels are thought to be multifactorial [3,14]. First, the presence of anemia and CKD may be directly associated with the progression of CAD and myocardial ischemia [3,10,14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations